2020
DOI: 10.1111/cas.14682
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine to prevent cervical intraepithelial neoplasia in Japan: A nationwide case‐control study

Abstract: Cervical cancer remains among the most common cancers in women worldwide and can be prevented by vaccination. The Ministry of Health, Labour and Welfare of Japan suspended active recommendation of regular human papillomavirus (HPV) vaccines in 2013 because of various symptoms including chronic pain and motor impairment. This nationwide case‐control study from April 2013 to March 2017 targeted women aged 20‐24 years old at cervical screening. We compared HPV vaccination exposure between those with abnormal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…Although there were four cases with CIN3+, none was in the inoculation group. Recently, Ikeda et al also reported that the nationwide case–control study in Japan demonstrated a risk reduction of 58% for CIN1+ and 75% for CIN2+ among women with versus those without HPV vaccination 17 . Ozawa et al also reported that the rates of CIN3+ were 0% (0/1002) with vaccination and 0.18% (9/4922) without vaccination in Japan 18 …”
Section: Discussionmentioning
confidence: 96%
“…Although there were four cases with CIN3+, none was in the inoculation group. Recently, Ikeda et al also reported that the nationwide case–control study in Japan demonstrated a risk reduction of 58% for CIN1+ and 75% for CIN2+ among women with versus those without HPV vaccination 17 . Ozawa et al also reported that the rates of CIN3+ were 0% (0/1002) with vaccination and 0.18% (9/4922) without vaccination in Japan 18 …”
Section: Discussionmentioning
confidence: 96%
“…HPV vaccination led to a significant reduction in the incidence of abnormal cytology in vaccinated women born in 1994-1995 [32]. In a case-control study the size of one-tenth of the total Japanese population, a preventive effect of CIN2 was reported [33]. In research conducted in Matsuyama City, a preventive effect of CIN3 was reported [34].…”
Section: Safety and Efficacy Of Hpv Vaccinationmentioning
confidence: 98%
“…In June 2013, only two months after inclusion in the NIP, the Ministry of Health, Labour, and Welfare announced that, although the vaccine would remain in the NIP and would be free for 12–16-year-old girls, all proactive recommendations for it would be suspended. Over the past eight years, several large-scale epidemiological studies conducted in Japan have shown that the HPV vaccine is effective against both HPV infection [ 6 ] and precancerous disease [ 7 8 ], and safe [ 9 ]. However, as of May 2021, the situation remains unchanged, with the vaccine still available for free to the target age groups but not being proactively recommended.…”
Section: Target 1: Hpv Vaccinationmentioning
confidence: 99%